Isolation and Characterisation of Chitin and Chitosan from Local Sources: Chitin and Chitosan Isolation from Shrimp and Crab - Aftab, Tayyaba; ullah, Asad; Iqbal, Muhammad Khalid; Khan, Rauf Ahmed; Chaudhry, Muhammad Nawaz (Biological Sciences - PJSIR, 2014)